The TikTok Platform as an Effective Medium for Disseminating Islamic Propagation Among Young People - Cici Cahyani (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Today's information world seems inseparable from technology. The use of technology by society has made the world increasingly sophisticated. Communication, which once required lengthy delivery, is now incredibly fast and seemingly distanceless. Advances in technology and information have given rise to da'wah activities through online media, such as social media. Preachers utilize various social media applications, one of which is TikTok. With this rapid technological advancement, TikTok is considered an alternative medium for delivering da'wah. Given its current popularity among young people, TikTok is being utilized to create new innovations in da'wah, conveying da'wah values ​​in a simple yet engaging manner. This is packaged in content tailored to current viral trends. Various da'wah video content is also created to encourage goodness in a more practical way, in video format, thus attracting TikTok users, the majority of whom are young people or teenagers who are in need of Islamic da'wah or moral education in an Islamic and modern way.